Scientific Opinion on application EFSA‐GMO‐BE‐2013‐118 for authorisation of genetically modified maize MON 87427 × MON 89034 × 1507 × MON 88017 × 59122 and subcombinations independently of their origin, for food and feed uses, import and processing submitted under Regulation (EC) No 1829/2003 by Monsanto Company. (1st August 2017) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: In this opinion, the GMO Panel assessed the five‐event stack maize MON 87427 × MON 89034 ×1507 × MON 88017 × 59122 and its 25 subcombinations, independently of their origin. The GMO Panel has previously assessed the five single events combined to produce this five‐event stack maize and 11 subcombinations of these events and did not identify safety concerns. No new data on the single events or their previously assessed subcombinations, leading to modification of the original conclusions were identified. The combination of the single events and of the newly expressed proteins in the five‐event stack maize did not give rise to issues – based on the molecular, agronomic/phenotypic or compositional characteristics – regarding food and feed safety and nutrition. Considering the scope of this application, the known biological function of the newly expressed proteins and the data available for the five‐event stack maize and its previously assessed maize subcombinations, the GMO Panel considered that different combinations of the single events would not raise environmental concerns. The GMO Panel concludes that the five‐event stack maize is as safe and as nutritious as the non‐genetically modified (GM) comparator and the tested non‐GM reference varieties in the context of its scope. For the 14 maize subcombinations for which no experimental data were provided, the GMO Panel assessed the likelihood of interactions among the single events, and concluded that their combinations would not raise safety concerns. These maize subcombinations are therefore expected to be as safe as the single events, the previously assessed subcombinations and maize MON 87427 ×MON 89034 × 1507 × MON 88017 × 59122. Since the post‐market environmental monitoring plan for the five‐event stack maize does not include any provisions for the 14 maize subcombinations not previously assessed, the GMO Panel recommended the applicant to revise the plan accordingly.